Different paths, same destination, yet diverse effects: Antecedent configurations and performance implications of digital transformation in pharmaceutical manufacturing enterprises——Evidence from Chinese listed companies - Shi, Bingxiao; Mou, Chunlan; Zhang, Yiwen; Cui, Tiantian (PloS one, 2025)
The empowerment of the real economy through digital technology has emerged as a crucial force in driving enterprises toward high-quality development. Identifying effective strategies to accelerate the digital transformation of pharmaceutical manufacturing enterprises is essential for their upgrading and sustainable growth. This study adopts a configurational perspective, drawing on the Technology-Organization-Environment (TOE) theoretical framework. It integrates fuzzy-set qualitative comparative analysis (fsQCA) and propensity score matching (PSM) to explore the driving pathways of digital transformation in pharmaceutical manufacturing enterprises and further analyzes how distinct configurations influence firm performance. The research findings reveal three pathways to achieving a high level of digital transformation: “opportunity-perception”, “predatory-competition”, and “innovation-fueled”. However, there is significant variability in the impact of these three pathways on firm performance. These pathways collectively exemplify the concept of “different paths, same destination, yet diverse effects”. Sample enterprises exhibit inadequate investment in digital technology innovation; enterprise size, executives’ risk appetite and government support intensity emerge as significant facilitators of the digital transformation process within pharmaceutical manufacturing firms, while technological integration capabilities positively enhance the effectiveness of this transformation; An overreliance on the external environment will constrain the innovation autonomy of pharmaceutical manufacturing enterprises during digital transformation and hinder the scale effects of these enterprises. The conclusion offers pragmatic guidance for pharmaceutical manufacturing enterprises without digital technology innovation capabilities to select suitable digital transformation strategies to enhance enterprise performance.